STUDIES ON THE ISOLATION OF METAPHASE CHROMOSOMES - ChoraŻy, M. (The Rockefeller University Press, 1963)
A method for the isolation of metaphase chromosomes from mouse L1210 leukemia cells has been developed. Cells, arrested at metaphase with colchicine, were exposed to hypotonic solution and the pH was then adjusted to 5.6 to stabilize the chromosomes. The metaphase figures were subsequently disrupted and the chromosomes isolated by a series of differential centrifugations in sucrose. The isolated chromosomes were well preserved, as judged by morphological criteria. The effect of various enzymes and chemical agents on the isolated chromosomes was studied. Chymotrypsin, trypsin, and deoxyribonuclease caused a marked disintegration of the chromosomes, whereas treatment with pepsin and ribonuclease induced no significant morphological alterations.